Some iterative methods for coincidence points of two continuous functions on closed interval - Nirunruttanakit S. (2017)
© 2017 by the Mathematical Association of Thailand. All rights reserved. In this paper, we introduce and study an iterative method, called SN-iteration, for approximating a coincidence point of two continuous functions on closed interval in R. A necessary and sufficient condition for convergence of the proposed method is presented. Moreover, we compare the rate of convergence between SN-iteration and W-iteration. Some numerical examples supporting our main results are also given.